A stereoselective total synthesis of (±)-tormesol - Kim, H; Bae, H; Kim, S; Kim, D; Lee, D; Paton, R (Elsevier, 2011)
A general strategy for the synthesis of both trans/syn- and trans/anti-sphenolobane diterpenes has been developed, which utilizes an intramolecular ester enolate alkylation (IEEA) as a key step. A stereoselective total synthesis of (±)-tormesol (1), an unusual trans/syn-sphenolobane diterpene, was accomplished in 18 steps in 4.1% overall yield from readily available aldehyde 16. © 2011 Elsevier Ltd. All rights reserved.